Dakwah Pada Media Baru Analisis Deskriptif Pada Akun TikTok Husain Basyaiaban - Muthmainnah, Maulida; Ridwan, Aang; Yuningsih, Yuyun (Tabligh: Jurnal Komunikasi dan Penyiaran Islam, 2024)
This study aims to determine the da’wah methods, da’wah materials, the advantages and disadvantages of Husain Basyaiban’s da’wah on the TikTok application.The research methodology used in this research is descriptive qualitative analysis. From the results of this study it can be seen that the da’wah method used by Husain for preaching is in accordance with Q.S An-Nahl verse 125, namely the method of da’wah bil wisdom, mau’idzatul hasanah and mujilah, the material used is related to material aqidah, shari’ah, and morals. The advantage of Husain Basyaiban’s da’wah is that his preaching style is interesting and easy to understand. The drawback is that the delivery is too fast.